THAILAND’S HEDGING STRATEGY UNDER THE STRATEGIC COMPETITION BETWEEN CHINA AND THE UNITED STATES - Feng, Yongping; Netkhunakorn, Chanattaporn (Berumpun: International Journal of Social, Politics, and Humanities, 2024)
Thailand's foreign policy stance has shifted dramatically since the Prayuth regime staged a coup in 2014. The purpose of this study: 1) Complement and expand on the theoretical meaning of hedging strategy. 2) It can theoretically support Thailand in the face of strategic conflict between China and the United States. 3) Be aware of why Thailand implements a hedging strategy and know the specific performance of Thailand’s hedging strategy. 4) It will aid in the growth of Thailand's connections with the two big countries. 5) This article can provide certain reference for research related to Thailand’s diplomatic strategy. The method of this study adopts content documentary analysis, case analysis method, literature research and historical method. According to the findings of this study, Thailand has begun to tilt more toward requesting assistance from China in Prayuth goverment. Many researchers are concerned about Thailand's neutrality. However, Thailand has not yet vanished from the United States. Just a few steps removed from the Obama and Trump administrations. Thailand has begun to rebuild its old friendship with America as the Joe Biden era looms. But anyway Thailand cannot choose a side. Because Thailand is a reliable ally on both sides. This has caused the Prayut government to seek cooperation from other organizations and countries, including Japan, India, and ASEAN. Thailand has accelerated the development of economic links with Japan. Accelerate the political development of relations with India. and establishing ties with ASEAN and Southeastern countries in order to find a way for small countries to maintain their own interests as much as possible in the fight between the two superpowers. Although hedging techniques are currently the preferred option for smaller countries, the variables driving this strategy differ. In Thailand, the majority of the factors that influence hedging tactics originate within the country. But all bordering countries are influenced by foreign causes. As a result, Thailand has become another special case of hedging among ASEAN countries.